PENGARUH KEMASAN PRODUK, BRAND IMAGE, DAN HARGA PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA CONATO BAKERY SITUBONDO - Rahayu, Ade Sekar Sri; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2024)
In today's era of global trade, there is intense competition in marketing products and services. Marketing plays a vital role in the business landscape, mainly because it focuses on the community's needs, especially consumers. The business environment is developing dynamically, along with changes in consumer preferences and the surrounding ecosystem. As consumer demand increases, this provides opportunities for businesses to innovate and meet the needs, desires, and expectations that continue to grow. The purpose of this study is to analyze and test the influence of Product Packaging, Brand Image and Product Price on Consumer Satisfaction Through Purchasing Decisions as Intervening Variables at Conato Bakery Situbondo using the simple random sampling method. Data analysis and hypotheses using the Partial Least Squares Structural Equation Modeling (PLS- SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that Product Packaging has a significant positive effect on Purchasing Decisions. Brand Image has a negative but not significant effect on Purchasing Decisions. Product Price has a significant positive effect on Purchasing Decisions. Product Packaging has a positive but not significant effect on Consumer Satisfaction. Brand Image has a positive but not significant effect on Consumer Satisfaction. Product Price has a positive but not significant effect on Consumer Satisfaction. Purchasing Decisions have a significant positive effect on Consumer Satisfaction. Product Packaging has a significant positive effect on Consumer Satisfaction through Purchasing Decisions. Brand Image has a negative but not significant effect on Consumer Satisfaction through Purchasing Decisions. Product Price has a significant positive effect on Consumer Satisfaction through Purchasing Decisions.